Conselhos afetivos em tempos de cultura terapêutica: analisando manuais de autoajuda e experiências das leitoras - Albuquerque, Rossana Maria Marinho (2015)
The thesis discusses the dissemination of affective advice manuals in Brazil from the analysis of best seller books Why men don t listen & women can t read maps, What smart women know, Why men love bithes and Seduction: a two-way road as well as the experiences of 23 readers interviewed for the research, by locating them in age, education, profession, regional origin, class, race, sexual orientation, marital status, among other aspects. Considering the experiences of readers regarding the manuals, two classification groups were established: 1) those that read, identified themselves with the contents of the books and adopted the advices in everyday life, changing their behavior as oriented by the manuals; 2) those that did not identified themselves or that changed their opinion about the books in another stage of life. In both cases, the main reason for reading the manuals was the need for emotional guidance in the search for long-lasting relationships. Among the uses of the advices identified in the account of the readers, was observed the emotional management, through which women sought to rationalize feelings, to avoid loving suffering in the process of affective pair choosing. The research starts from the emotional dimension, represented by the analysis of manuals and interviews with readers, seeking to observe the existing mediations in the studied phenomenon, which relates to therapeutic discourse, notions of individualism, feminism influences, mass culture, market relations and consumption. The manuals provide emotional advice that promise solutions to love life and by observing the experiences of readers, it is identified that the search by the books is also explained due to position management required to women today when they try to conciliate the scopes of emotion, family and work. By analyzing the emotional cost experienced by women and the solutions offered by advice literature, this research discusses implications in gender relation aspects in the current context.